Climate Change, Forestry and Carbon Financing in Nepal: Editorial Introduction - Ojha, Hemant R (Journal of Forest and Livelihood, 2009)
Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.1-3